Reliability and Validity of International Large-Scale Assessment Understanding IEA's Comparative Studies of Student Achievement - Wagemaker, Hans (IEA Research for Education, 2020)
This open access book describes and reviews the development of the quality control mechanisms and methodologies associated with IEA's extensive program of educational research. A group of renowned international researchers, directly involved in the design and execution of IEA's international large-scale assessments (ILSAs), describe the operational and quality control procedures that are employed to address the challenges associated with providing high-quality, comparable data. Throughout the now considerable history of IEA's international large-scale assessments, establishing the quality of the data has been paramount. Research in the complex multinational context in which IEA studies operate imposes significant burdens and challenges in terms of the methodologies and technologies that have been developed to achieve the stated study goals. The demands of the twin imperatives of validity and reliability must be satisfied in the context of multiple and diverse cultures, languages, orthographies, educational structures, educational histories, and traditions. Readers will learn about IEA's approach to such challenges, and the methods used to ensure that the quality of the data provided to policymakers and researchers can be trusted. An often neglected area of investigation, namely the consequential validity of ILSAs, is also explored, examining issues related to reporting, dissemination, and impact, including discussion of the limits of interpretation. The final chapters address the question of the influence of ILSAs on policy and reform in education, including a case study from Singapore, a country known for its outstanding levels of achievement, but which nevertheless seeks the means of continual improvement, illustrating best practice use of ILSA data.